HIV Stigma and Viral Suppression Among People Living With HIV in the Context of Universal Test and Treat: Analysis of Data From the HPTN 071 (PopART) Trial in Zambia and South Africa. (15th December 2020) - Hargreaves, James R.; Pliakas, Triantafyllos; Hoddinott, Graeme; Mainga, Tila; Mubekapi-Musadaidzwa, Constance; Donnell, Deborah; Piwowar-Manning, Estelle; Agyei, Yaw; Mandla, Nomhle F.; Dunbar, Rory; Macleod, David; Floyd, Sian; et al.
Abstract : Background: The impact of HIV stigma on viral suppression among people living with HIV (PLHIV) is not well characterized. Setting: Twenty-one communities in Zambia and South Africa, nested within the HPTN 071 (PopART) trial. Methods: We analyzed data on viral suppression (<400 copies HIV RNA/mL) among 5662 laboratory-confirmed PLHIV aged 18–44 years who were randomly sampled within the PopART trial population cohort 24 months after enrolment (PC24). We collected data on experiences and internalization of stigma from those PLHIV who self-reported their HIV status (n = 3963/5662) and data on perceptions of stigma from a 20% random sample of all PLHIV (n = 1154/5662). We also measured stigma at the community-level among PLHIV, community members, and health workers. We analyzed the association between individual- and community-level measures of HIV stigma and viral suppression among PLHIV, adjusting for confounding. Results: Of all 5662 PLHIV, 69.1% were virally suppressed at PC24. Viral suppression was highest among those 3963 cohort participants who self-reported living with HIV and were on ART (88.3%), and lower among those not on treatment (37.5%). Self-identifying PLHIV who reported internalized stigma were less likely to be virally suppressed (75.0%) than those who did not (80.7%; adjusted risk ratio, 0.94 95% CI: 0.89 to 0.98). Experiences, perceptions, and community-level measures of stigma were not associated with viral suppression. Conclusion: Internalized stigma among PLHIV was associated with a lower level of viral suppression; other dimensions of stigma were not. Stigma reduction approaches that address internalized stigma should be an integral component of efforts to control the HIV epidemic. Abstract : Supplemental Digital Content is Available in the Text.